Operational performance of crystal collimation with 6.37 Z TeV Pb ion beams at the LHC - M. D’Andrea; O. Aberle; R. Bruce; M. Butcher; M. Di Castro; R. Cai; I. Lamas; A. Masi; D. Mirarchi; S. Redaelli; R. Rossi; W. Scandale (Physical Review Accelerators and Beams, 2024)
The concept of crystal collimation relies on the use of bent crystals to coherently deflect positively charged particles with suitable impact conditions by trapping them in the potential well generated by adjacent crystalline planes. The resulting deflection is much higher than what can be achieved by multiple scattering on amorphous materials. For this reason, this technique has been explored in the past decades for applications to particle accelerators. In particular, a full test stand was installed in the betatron collimation insertion of the Large Hadron Collider (LHC) to explore applications to hadron beam collimation. This setup was extensively studied in Run 2 (2015–2018), as a way to improve the cleaning performance of the machine in particular with Pb ion beams, in view of the more challenging parameters envisaged for the High Luminosity upgrade (HL-LHC). This paper reports the results of measurements performed with Pb ion beams, demonstrating the capability of crystal collimation to improve the cleaning performance at the LHC. These results supported the integration of this advanced technology in the baseline upgrade program for HL-LHC.